Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology, 2025)
Support is a vital resource at every stage of development throughout the lifespan. In the mother-child relationship, the exchange of support is subject to change in relation to the tasks and framework conditions of the current phase of life. While values and norms typically include social expectations, attitudes summarize individual thoughts or feelings. During young adulthood and midlife, attitudes are particularly important for the mutual support between mothers and their adult children when there are no practical framework conditions, such as care needs, that necessitate support. This study uses social exchange theory to examine the mediating role of felt obligation and perceived mutual reciprocity as important attitudes in the well-known relation between mothers and their adult children receiving and giving support. The sample consisted of 598 German adults (aged 20–49, 55.2% female) and 577 mothers (aged 40–87) of these adults; both perspectives were taken into account. The results from the parallel mediation analyses, in which instrumental and emotional support were considered separately, showed a mediating effect of felt obligation on the instrumental support of adult children for their mothers. The emotional support received and given by the adults to their mothers was mediated by felt obligation and perceived mutual reciprocity. The received and given instrumental and emotional support of the mothers to their adult children was mediated by perceived mutual reciprocity. The relevance of the adults' and mothers' different attitudes regarding support later in life is discussed.